2020
DOI: 10.1101/2020.09.10.288548
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Susceptibility of domestic swine to experimental infection with SARS-CoV-2

Abstract: SARS-CoV-2, the agent responsible for COVID-19 has been shown to infect a number of species. The role of domestic livestock and the risk associated for humans in close contact remains unknown for many production animals. Determination of the susceptibility of pigs to SARS-CoV-2 is critical towards a One Health approach to manage the potential risk of zoonotic transmission. Here, pigs undergoing experimental inoculation are susceptible to SARS-CoV-2 at low levels. Viral RNA was detected in group oral fluids and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 22 publications
0
19
1
Order By: Relevance
“…Likewise, pigs could not be infected with SARS-CoV-2 intranasally [ 64 ]. This work contrasts with a study showing the live virus isolated from oronasally infected pigs and the development of a humoral immune response [ 65 ]. Others have shown that pig airway epithelial cells do not support the viral replication [ 18 ].…”
Section: Further Experimental Proof Of Permissiveness To Infectioncontrasting
confidence: 70%
“…Likewise, pigs could not be infected with SARS-CoV-2 intranasally [ 64 ]. This work contrasts with a study showing the live virus isolated from oronasally infected pigs and the development of a humoral immune response [ 65 ]. Others have shown that pig airway epithelial cells do not support the viral replication [ 18 ].…”
Section: Further Experimental Proof Of Permissiveness To Infectioncontrasting
confidence: 70%
“…Additionally, experimental inoculation demonstrated the susceptibility of non-human primates, ferrets, minks, cats, dogs, raccoon dogs, golden Syrian hamsters, deer mice, and white-tailed deer as evidenced by mild to moderate clinical disease and/or sustained viral replication, suggesting a productive infection after inoculation with SARS-CoV-2 [ 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Whereas experimental inoculation of swine, cattle, poultry, and fruit bats have shown that these species are either not susceptible to SARS-CoV-2 or that inoculation did not result in productive infection and sustained viral replication [ 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The science on SARS-CoV-2 is evolving rapidly and shows inconsistent findings on the potential role of pigs in SARS-CoV-2 epidemiology. While two experiments showed that juvenile pigs were not susceptible to SARS-CoV-2 inoculated at < 10 6 PFU ( Meekins et al, 2020 ; Shi et al, 2020 ), a more recent experiment showed that SARS-CoV-2 does replicate at low levels in 8 week old domestic pigs when inoculated oronasally at 10 6 PFU ( Pickering et al, 2020 ) and that SARS-CoV-2 does infect and cause damage to cultured porcine cells ( Meekins et al, 2020 ). Similarly, while multiple studies have demonstrated that pig ACE2 receptors (a mechanism of viral entry into host cells) show high affinity for SARS-CoV-2 spike protein binding ( Wan et al, 2020 ; Zhai et al, 2020 ; Zhao et al, 2020 ), another suggests that pig ACE2 should have low compatibility for SARS-CoV-2 ( Damas et al, 2020 ).…”
Section: Why Might Pigs Contribute To Emergence Of Zoonotic Covs?mentioning
confidence: 99%